2021
DOI: 10.1177/20458940211006289
|View full text |Cite
|
Sign up to set email alerts
|

L‐citrulline increases arginase II protein levels and arginase activity in hypoxic piglet pulmonary artery endothelial cells

Abstract: The L-arginine precursor, L-citrulline, re-couples endothelial nitric oxide synthase (eNOS), increases nitric oxide (NO) production, and ameliorates chronic hypoxia-induced pulmonary hypertension (PH) in newborn pigs. L-arginine can induce arginase, which, in turn, may diminish NO production. Our major purpose was to determine if L-citrulline increases arginase activity in hypoxic piglet pulmonary arterial endothelial cells (PAECs), and if so, concomitantly impacts the ability to increase eNOS re-coupling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 39 publications
3
17
1
Order By: Relevance
“…However, we were concerned with the possibility of uncovering adverse events from using higher L‐citrulline doses. One possible adverse consequence, raised by our recent in vitro findings (Douglass et al, 2021 ), is that progressively increasing the dose of L‐citrulline would elevate arginase activity to levels adversely impacting NO signaling. We were also mindful that newborns with chronic lung and heart diseases sometimes develop pulmonary edema when given high fluid volumes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, we were concerned with the possibility of uncovering adverse events from using higher L‐citrulline doses. One possible adverse consequence, raised by our recent in vitro findings (Douglass et al, 2021 ), is that progressively increasing the dose of L‐citrulline would elevate arginase activity to levels adversely impacting NO signaling. We were also mindful that newborns with chronic lung and heart diseases sometimes develop pulmonary edema when given high fluid volumes.…”
Section: Discussionmentioning
confidence: 94%
“…It is possible that higher doses of L‐citrulline might further reduce PVR and enhance NO production in vivo in hypoxic piglets. However, we recently performed in vitro studies and found that L‐citrulline dose‐dependently increases arginase activity in hypoxic piglet pulmonary artery endothelial cells (Douglass et al, 2021 ). This latter finding is concerning because arginase can decrease NO production by competing with eNOS for the substrate, L‐arginine (Akashi et al, 2001 ; Morris, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…For arginase I and II and eNOS analysis, using previously described methods, aliquots of supernatant were applied to tris‐glycine precast 4%–20% polyacrylamide gels so that equal amounts of protein were loaded. 16 After electrophoresis at 120 volts for 2 h, the protein was transferred to a polyvinylidene difluoride membrane. Nonspecific protein binding was blocked by incubating the membrane at room temperature in PBS and 0.1% Tween‐20 (PBS‐T; Sigma‐Aldrich) containing 5% nonfat dried milk and then washing in PBS‐T containing 1% nonfat dried milk.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the loss of the mitochondrial uncoupled protein (UCP2) in endothelial cells caused increased PINK1 and Parkin 49 . Arginase II protein (ArgII) regulates Parkin-dependent p32 degradation and it contributes to eNOS activation 50 . USP30 is an OMM-localized deubiquitinase that antagonizes PINK1/Parkin-driven mitophagy in mammalian cells by deubiquitinating the OMM substrate.…”
Section: Parkinmentioning
confidence: 99%